Experimental study on crack width and crack spacing for Glass-FRP reinforced concrete beams. (15th January 2017) - Barris, C.; Torres, L.; Vilanova, I.; Miàs, C.; Llorens, M.
Highlights: The experimental cracking behaviour of 15 GFRP RC flexural members is presented. Crack width and spacing are measured by digital image correlation technique. Different patterns of crack width along the height of the crack are obtained. Mean crack width is affected by the Ef, ρ, d and bond behaviour. Bond coefficients are adjusted for different existing formulations. Abstract: Fibre Reinforced Polymers (FRP) have been proven to be adequate substitutes for steel reinforcement under aggressive environments for flexural Reinforced Concrete (RC) elements. Their mechanical properties, basically their lower modulus of elasticity, derive in larger crack widths and deflections, in particular when Glass-FRP (GFRP) bars are used. Moreover, their different bond behaviour, mainly due to their mechanical properties and different surface configurations, make necessary to assess the available equations to determine crack width need to be assessed. This paper presents a study on the cracking behaviour of GFRP RC elements based on the results of an experimental programme involving 15 beams. The paper studies the influence of the reinforcing material, ϕ / ρeff ratio, concrete cover, stirrup spacing and bond between the concrete and the reinforcement. For this purpose, two different types of GFRP and steel bars were used. The cracking behaviour (crack width and spacing) in the pure bending zone was analysed up to the service load. Crack width was consistently acquired by using a Digital Image Correlation (DIC) technique. The 2D full-field displacements of the pure flexural zone were registered using 4 digital cameras and commercial software that enables the evolution of the specimen cracks to be analysed. Finally, bond coefficients have been adjusted to different formulations in terms of crack spacing and crack width.